IDENTIFIKASI BAHAN PENGAWET FORMALIN DAN BORAK PADA BEBERAPA JENIS MAKANAN YANG BEREDAR DI PEKALONGAN - Kharimatul Khasanah; Siska Rusmalina (LPPM Universitas Pekalongan, 2019)
Formaldehyde and Boris acid are dangerous preservatives which are added to many types of food by irresponsible traders Formaldehyde is used because the price is relatively cheap and it can make food last a long time, while borax can also increase suppleness and give a savory taste. The use of formaldehyde and borax additives violates RI Regulation No. 033 of 2012 concerning prohibited food additives. The danger of continual exposure to formaldehyde and borax can cause respiratory irritation, nausea, vomiting, diarrhea, cell changes / cell death that can lead to cancer and death. The purpose of this study was to determine the presence of formalin in several types of food circulating in the city / district of Pekalongan from 2018 to 2019. The samples used were wet noodles, meatballs, salted fish, tofu, and brains. Formalin testing was carried out qualitatively using Schiff reagents by observing the color changes that occur. And qualitative testing of borax by flame test and turmeric test. The results showed that in 2018 and 2019 the level of use of formalin was high with a percentage above 40% and the use of boric acid around 12.5-13.33% so it could be said to be unfit for consumption and not good for health.